Health economic evaluations of medical tests: Translating laboratory information into value – A case study example. (January 2022) - Jülicher, Paul; O'Kane, Maurice; Price, Christopher P; Christenson, Robert; John, Andrew St
Health-care providers and funders are focused on identifying value in all their services and that includes laboratories. This means that in order to gain a share of scarce resources, laboratory professionals must also understand and assess the value of tests and that includes their economic impact. This can be assessed using health economic modelling tools which, when used in conjunction with a detailed value proposition for the test, can translate laboratory information into value. While a variety of health economic assessment tools are available, this review will focus on the use of decision analytic models which essentially compare the outcomes from pathways with and without the new test, the value of which is being assessed. A step-by-step framework is provided to guide laboratory professionals through the essential steps of conducting the evaluation. Initial steps include mapping the clinical pathway, understanding the goal of the evaluation, identifying the key stakeholders and their needs and determining a suitable analytical model. Following collection of the actual data, the validity of the model must be checked, and the robustness of the outcomes tested through sensitivity analysis. The last step is to translate the findings into measures of value which can then inform appropriate decisions by the stakeholders. This review of basic health economic modelling should enable laboratory professionals to have an understanding of how modelling can be applied to tests in their own environment and help deliver their potential value.